Пассивные конструкции в связном тeкcтe - Лауринавичене, В.; Вовшин, Я. М. (Kalbotyra, 1978)
The article deals with the role of passive constructions in discourse. Passive constructions may be considered to be used as a means of structural and semantic coherence of the constituent units of discourse. On the other hand, the use of passive constructions is stimulated by the structure of discourse.